Business dynamics in information technology - Gottschalk, Petter, 1950- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2007)
"This book presents business-technology alignment processes, interaction processes, and decision making processes, in order to help the reader study information technology from a dynamic, rather than a static, perspective. By introducing two simple tools from system dynamic modeling - causal loops and reference modes - the dynamic perspective will become important to both students and practitioners"--Provided by publisher.